Open innovation culture and product development in a South African telecommunications operator - Shonhiwa, Prince (University of the Witwatersrand, Johannesburg, 2023)
To increase the rate of innovation during product development, telecommunications organizations are increasingly adopting open innovation strategies. Open innovation is viewed as an important business and national strategy in developing nations like South Africa to overcoming structural barriers and resource limitations. A supportive organizational culture that encourages the bi-directional flow of knowledge inside and outside the organization is necessary for open innovation to endure. The aim of the study is to understand how South African telecommunications companies can develop organizational cultures that support open innovation during the development of their products. Research findings indicate that South African telecommunications providers understand the cultural attributes that are crucial for open innovation, and there is evidence of their existence to some degree. However, supportive organizational structures and capabilities must be developed to enable open innovation to mature
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Innovation; Organizational Culture; Innovation Culture; Open Innovation; Open Innovation culture; Telecommunications; Product Management; Product development; UCTD; SDG-9: Industry, innovation and infrastructure